2017
DOI: 10.3892/etm.2017.5302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water extracts of Rehmannia glutinosa on antioxidant system of Nrf2 in paraquat-induced insulin resistance diabetic rat model

Abstract: The objective of this study was to observe the effects of water extracts of Rehmannia glutinosa on the antioxidant system of Nrf-2 in diabetic mice induced by paraquat, and to provide the basis for its further development. Thirty male mice were randomly divided into the control group, model group and observation group. The mice in the model group and the observation group were treated with paraquat to induce insulin resistance, with the control group injected with the same volume saline. After the model establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…and Bentonite [22] Reduce absorption [19][20][21][22] Rhubarb [23] Eliminate and reduced absorption of paraquat [23] Immunosuppressive (cyclophosphamide and corticosteroids) [19] Vitamins C, E and N-acetylcysteine [19] Naringin, Edaravone, Quercetin [19] Lysine acetylsalicylate (a salt of aspirin) [19] Anti-C5a antibodies such as IFX-1 [24] Type III procollagen peptide [25] Rapamycin [26] Procyanidin B2 [27] Doxycycline [28] Rosiglitazone [29] Silymarin [30] ω-3 fish oil emulsion [31] Ambroxol [32] Atorvastatin [33] Alpha lipoic acid [34] Sodium tauroursodeoxycholate [35] 1-methylhydantoin (MH) [36] Metformin [37] Anti-inflammatory and anti-oxidative properties [19,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]: Medicines [19,[24][25][26]…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…and Bentonite [22] Reduce absorption [19][20][21][22] Rhubarb [23] Eliminate and reduced absorption of paraquat [23] Immunosuppressive (cyclophosphamide and corticosteroids) [19] Vitamins C, E and N-acetylcysteine [19] Naringin, Edaravone, Quercetin [19] Lysine acetylsalicylate (a salt of aspirin) [19] Anti-C5a antibodies such as IFX-1 [24] Type III procollagen peptide [25] Rapamycin [26] Procyanidin B2 [27] Doxycycline [28] Rosiglitazone [29] Silymarin [30] ω-3 fish oil emulsion [31] Ambroxol [32] Atorvastatin [33] Alpha lipoic acid [34] Sodium tauroursodeoxycholate [35] 1-methylhydantoin (MH) [36] Metformin [37] Anti-inflammatory and anti-oxidative properties [19,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]: Medicines [19,[24][25][26]…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…and has been used in ancient China for Xiao-ke symptom (a synonym of current DM name in traditional Chinese medicine). Although RG and CC alone had good therapeutic effects on diabetes and its complications [15,16,17,18], CC served as a sovereign drug while RG as a minister drug [19]. Rodent model-based experiments showed that their combined use had better pharmacological and therapeutic effects on diabetes than its single herb [19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%